Managing industry enabled e-government: lessons learned from the IT industry in Taiwan. (28th October 2004) - Chou, Tzu-Chuan; Hsu, Li-Ling
The emerging new form of e-government provides public services with the means to gain and retain competitiveness in a complex and turbulent global political environment. However, the way in which e-government initiatives link policies that promote the IT industry and, in turn, support the evolution of e-government has not yet been onvincingly demonstrated. To address this gap, this paper focuses on the concept of "industry enabled e-government" to study the development of e-government and suggests that the policies of e-government and promotion of IT industrial transformation are dual cores for a government seeking an information based society. A case study is presented and serves to identify the industry–government interaction. The study suggests that factors including technology development and standards setting, key performance index setting, private–public partnerships and learning should be taken into account in developing e-government. An extension of these findings leads to four research propositions for the development of e-government and the implications of policy making for IT industries are discussed.